Analysis of Cellphone Use on Biology Learning Outcomes of Class XI IPA Students of SMA Negeri 1 Aek Natas - Afridayani, Afridayani; Simamora, Siti Suharni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to analyze the use of mobile phones by students of class XI IPA SMA Negeri 1 Aek Natas on student biology learning outcomes. The population in this study were all students of class XI IPA which contained 5 classes with a total of 149 students and the sample in this study was 45 students. Sampling in this study using random sampling (randomly). Data collection techniques in this study were using a questionnaire on the use of mobile phones and documentation of student biology learning outcomes. From the research conductedby distributing a questionnaire, which obtained the following results: On the indicator of ownership and time of using mobile phones 58%, on indicators of positive use of cellphones 90.67%, on indicators of negative use of cellphones 54.78%, indicators of cellphone use at school 77.08%, indicators of cellphone use at home 74.58 %.The results of this study indicate that the use of mobile phones can positively improve student biology learning outcomes.